2003
DOI: 10.1101/gr.1416703
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Modes of Microsatellite Mutation Processes: Evidence From the Complete Genomic Sequences of Nine Species

Abstract: We surveyed microsatellite distribution in 10 completely sequenced genomes. Using a permutation-based statistic, we assessed for all 10 genomes whether the microsatellite distribution significantly differed from expectations. Consistent with previous reports, we observed a highly significant excess of long microsatellites. Focusing on short microsatellites containing onlya few repeat units, we demonstrate that this repeat class is significantly underrepresented in most genomes. This pattern was observed across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 41 publications
7
130
2
1
Order By: Relevance
“…(Varshney et al 2005;Sharma et al 2007;Grover and Sharma 2011). However, the choice of microsatellite mining criteria and algorithms adopted for the purpose of screening genomic sequences for identifying microsatellites therein offer a lot of diversity (Toth et al 2000;Katti et al 2001;Dieringer and Schlotterer 2003;La Rota et al 2005). Each of the algorithm used in these studies fulfills a certain criteria and accordingly is based on a different principle.…”
mentioning
confidence: 99%
“…(Varshney et al 2005;Sharma et al 2007;Grover and Sharma 2011). However, the choice of microsatellite mining criteria and algorithms adopted for the purpose of screening genomic sequences for identifying microsatellites therein offer a lot of diversity (Toth et al 2000;Katti et al 2001;Dieringer and Schlotterer 2003;La Rota et al 2005). Each of the algorithm used in these studies fulfills a certain criteria and accordingly is based on a different principle.…”
mentioning
confidence: 99%
“…There is indication that repeat type and number of repeats have an influence on microsatellite variability (Ellegren, 2000;Dieringer and Schlotterer, 2003). To detect if this is the case in our two sets of data, we The expected homozygosity, (F ) in a sample of the same size and containing the same number of different alleles is calculated per Ewens' expectations using the package PyPop (Lancaster et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tracts less than eight nucleotides long seem resistant to slippage, suggesting that there is a critical size above which a homopolymeric tract can be subjected to slippage (Dechering et al 1998). However, computer simulations using analysis of genomic sequences in nine species suggested that short repeats, such as (C) 4 , might have a susceptibility to insertions and deletions 10-15-fold higher than nonrepetitive sequences (Dieringer and Schlotterer 2003). The present study shows that with homopolymeric runs of eight nucleotides or more, there is a tendency toward an increase in the frequency of the variations with the length of the run.…”
Section: Discussionmentioning
confidence: 99%